Spectacle adherence and barriers towards spectacle wear among primary school going children - Yadav, Rakesh Kumar; Rani, Anjali; Chander, Ashish (International Journal of Research in Medical Sciences, 2023)
Background: The aim of the study was to assess the spectacle adherence and barriers towards spectacle wear among primary school going children in the west UP. Methods: A cross-sectional, descriptive questionnaire-based study was conducted among the primary school going children in rural area of west UP. Spectacle was provided after the comprehensive eye examination, free of cost to the children those who required. An uninformed visit was planned after 3 months of initial examination to assess the compliance of spectacle wear and non-compliant subjects were questioned about the reasons for not wearing spectacle. Results: This study consists of total 158 children. In this study, majority of participants 88.61% were myopic having low degree of myopia being more common. Compliance rate towards the spectacle wear was high in males as compared to female children. Compliance rate was significantly varied with the age of participants. Myopic patients show more compliance than the hyperopic patients, it was insignificant while considering the severity of refractive error. The main cause for non-compliance towards spectacle was the cosmetic blemish. Conclusions: It has been found that the compliance rate towards the spectacle wear was not good enough even after distributing the spectacle free of cost to the children. Various factors including cosmetic blemish, parents and children perception for wearing spectacle and difficulties experienced by the children while wearing glasses were responsible for the non-compliance. The compliance rate can be increased by providing the education and training and Counselling to school teachers, children and their parents regarding the eye health.